Analisis Implementasi PAPSI dan PSAK Pada Produk Pembiayaan Multijasa Studi Kasus pada PT BPRS Pemkot Bekasi - Fajr Ramadhan; sfandayani . (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2012)
The purpose of this study was to determine and evaluate the application of accounting for the expenses multiservice PT. BPRS Bekasi City and the process is done in a multiservice financing. The method used is a naturalistic qualitative method with the primary data source is performed by a live interview to the relevant parties as well as secondary data obtained from related literature. This study refers to the Guidelines for Islamic Banking and Accounting Treatment Accounting Standards issued by the Indonesian Accounting Association and has been generally applied by banks in Indonesia. The conclusion from this study showed that the technique of recording and accounting treatment in the use of multiservice financing Ijara contract in accordance with PSAK and PAPSI. However, this listing has not been adopted purely and PAPSI direct of PSAK applicable. The accounting treatment in multiservice financing refers only to SFAS 107 on ijara because there are no specific PSAK governing the financing of multiservice.